Ethical consideration of gene therapy in Indonesian HIV patients and its management: A narrative review - Abidin, Ali Zainal; Lessy, Nina Sakina; Widiastuti, Melina Ayu; Abimanyu, I Gede Agni Marwan; Ramadhan, Raka Kurnia (Indonesian Journal of Pharmacology and Therapy, 2025)
Human Immunodeficiency Virus (HIV) infection remains a major global health issue, including in Indonesia. Gene therapy (GT) has emerged as a promising therapeutic approach for various diseases, including HIV. However, its application also raises significant ethical challenges, particularly within the Indonesian context. This article aims to explore the ethical considerations, potential, and challenges of implementing GT for patients with HIV in Indonesia. A comprehensive narrative review was conducted by examining currentscientific literature and ethical frameworks related to GT and HIV management, with a focus on clinical feasibility, safety, and social implications within the Indonesian context. Gene therapy technologies such as zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and ClusteredRegularly Interspaced Short Palindromic Repeats (CRISPR) have shown promising potential in suppressing HIV infection. However, concerns remain regarding onand off-target effects that may cause genomic instability and oncogenesis. Ethical challenges include the high cost of therapy, limited public understanding of GT,and the absence of specific regulations governing its application in HIV treatment. Indonesia’s diverse sociocultural landscape further complicates equitable access and acceptance of this advanced technology. The implementation of GT for HIV in Indonesia requires careful ethical consideration, transparent communication,and robust policy development. Establishing national guidelines and conducting further research are essential to ensure that the adoption of GT is safe, equitable, and ethically responsible within the Indonesian healthcare system.